Дослідження верхніх шарів пам’ятки Єзупіль І у 2008 р. - Гавінський, А.; Ленартович, О. (Інститут українознавства ім. І. Крип'якевича НАН України, 2009)
Results of explorations of upper cultural layers of Paleolithic site Yezupil’ I, based on excavations, carried out in 2008, are published at the article. Eight objects, dated back to different eras were discovered and large collection of artifacts was found. Collected materials belong to Linear pottery culture, Trypil’s’ka culture, Early Scythian Period and Praz’ka culture.